2021
DOI: 10.29103/ijevs.v3i3.4982
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Application of Inquiry Learning Approach in Classroom: Students Exploration of Changes in Understanding Meaningful Mathematical Concepts

Abstract: This study was intended to investigate the influence of inquiry learning approach assisted with square word media toward students’ mathematical understanding ability in learning mathematics. This study was conducted through quantitative research procedures namely quasi-experimental design. The populations were all students of class X at MAS Syamsuddhuha. The samples were 25 students of class X MIA 1 and 25 students of class X MIA 2, selected by purposive sampling. The nonequivalent posttest-only control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Mathematics teachers usually conduct their teaching process conventionally, namely through lectures and discussions; (Oyebanji & Idiong, 2021;Rahmatina & Zaid, 2019;Rind & Mughal, 2020;Winarso, 2018). They only focus on the concepts they prepared without involving students to be active in the learning process, making learning seem monotonous, and students only focus on completing their cognitive values without developing their characters and soft skills during the learning process in class (Akmalia et al, 2021;Joseph, 2020;Nazirah et al, 2021;NWOKE, 2021;Setiawaty et al, 2018;Sholli et al, 2020;Zaiyar et al, 2020). Observations in schools found that students are not accustomed to reflecting on the learning process because their teachers rarely train them to reflect on the learning experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematics teachers usually conduct their teaching process conventionally, namely through lectures and discussions; (Oyebanji & Idiong, 2021;Rahmatina & Zaid, 2019;Rind & Mughal, 2020;Winarso, 2018). They only focus on the concepts they prepared without involving students to be active in the learning process, making learning seem monotonous, and students only focus on completing their cognitive values without developing their characters and soft skills during the learning process in class (Akmalia et al, 2021;Joseph, 2020;Nazirah et al, 2021;NWOKE, 2021;Setiawaty et al, 2018;Sholli et al, 2020;Zaiyar et al, 2020). Observations in schools found that students are not accustomed to reflecting on the learning process because their teachers rarely train them to reflect on the learning experiences.…”
Section: Introductionmentioning
confidence: 99%
“…They do not understand how to prove the formulas. As a result, they find it difficult to solve problems more applicable (Akmalia et al, 2021;Chanafi et al, 2020;Mengistie, 2020;Muliyono et al, 2019;Nazirah et al, 2021;Prihatin et al, 2022;Puspitasari et al, 2019;Ruslimin et al, 2019;Sirait et al, 2020).…”
Section: Introductionmentioning
confidence: 99%